(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The tact, particularly in its metaphorical extension, is related with central elements in the clinical context such as the emotion, and the private and aversive events reports. Studies indicate at least five functions of the metaphor in the clinical context: 1) it allows the access to controlling variables of the client´s behavior; 2) it makes possible to tact private events ; 3) it promotes emotions; 4) it increases the verbal behavior efficacy, and 5) it facilitates the emission of responses that have been punished before. This study objectives were: 1) evaluate the relationship between the emission of metaphors and the client and therapist behaviors in a behavioral analytic therapy, considering the probable functions indicated by the literature, and 2) assess the metaphors and their relationships with indicators of clinical improvement, according to case conceptualization, comparing it between sessions with and without an activity aimed to evoke methaphors. Nine sessions were recorded and analyzed, an activity to enhance methaphors was introduced at the 6th session. Results suggests that the introduced activity increased considerably the emission of metaphors. Therapist and client metaphors had the function of describing client behavior variables. The metaphors emitted by the client had also described tacts of private events and aversive content. The metaphor verbalizations and clinical improvement behaviors were discussed. The results suggest that the metaphor has a significant role in describing behaviors variables, promote tacts of private events, and in an increase in the emission of verbal responses of aversive content.